Periodontal health status and influencing factors among 12- and 15-year-old adolescents: evidence from a cross-sectional study in Guizhou province, China (2019–2020) - Xinyue Chen; Ye Tang; Juanjuan Wu; Jiangling Sun; Xutong Zhang; Nanyang Zhao; Arsy Huda Fathaniard; Liangsa Zhang; Wei Li; Na Li; Taiming Dai; Liming Chen (BMC Oral Health)
Abstract Background At present, the lack of studies on adolescent periodontal health in Guizhou Province is not conducive to the formulation of periodontal policies for children. The purpose of this study was to understand the periodontal health status of adolescents aged 12 to 15 in Guizhou Province and to explore the factors that affect their periodontal health. Methods A total of 2,344 adolescents aged 12 and 2,356 adolescents aged 15 from 11 districts in Guizhou Province were selected using a multi-stage stratified random sampling method. Oral health examinations were performed and questionnaires were administered in accordance with the standards outlined in the Fourth National Epidemiological Survey on Oral Health and the WHO Basic Methods for Oral Health Surveys (5th edition). The chi-square test and binary logistic regression analysis explored periodontal health status and influencing factors. Results The rates of gingival bleeding in adolescents aged 12 and 15 were 69.5% and 66.4%, while the rates of calculus were 84.5% and 91.0%, binary logistic regression analysis showed that living region(12-year-olds, p = 0.033; 15-year-olds,p < 0.001), gender(15-year-olds,p < 0.001), ethnic groups(12-year-olds,p = 0.012; 15-year-olds,p = 0.001), smoking frequency(12-year-olds,p = 0.036; 15-year-olds,p = 0.011) and mother’s highest education(15-year-olds, p = 0.009) were related to gingival bleeding, while brushing teeth(12-year-olds, p = 0.002), dental caries(12-year-olds,p = 0.014), living region(15-year-olds,p = 0.005), mother’s highest education(15-year-olds, p = 0.025)and have you seen a dentist(15-year-olds,p = 0.030)were related to calculus. Conclusion Gingival bleeding and calculus among 12-year-old and 15-year-old adolescents in Guizhou Province are serious. This suggests that people should pay more attention to the risk factors of periodontal health, regularly examine their periodontal health, and provide supportive periodontal therapy to adolescents.